Numerical simulation study of the elastic properties of single-walled carbon nanotubes containing vacancy defects. (15th March 2016) - Sakharova, N.A.; Pereira, A.F.G.; Antunes, J.M.; Fernandes, J.V.
Abstract: The mechanical behaviour of non-chiral and chiral single-walled carbon nanotubes containing different percentage (up to 10%) and types of vacancy defects is studied under tensile, bending and torsional loading. A three-dimensional finite element model is used in order to evaluate the corresponding rigidities and, subsequently, Young's and shear moduli and Poisson's ratio. The three rigidities decrease with the increase of the percentage of vacancies. Also, the Young's and shear moduli and the Poisson's ratio of single-walled carbon nanotubes are sensitive to the presence of vacancy defects in nanotube: elastic moduli decrease and the Poisson's ratio increases with increasing of the percentage of vacancies. The moduli of single-walled carbon nanotubes with 10.0% of vacancy defects, when compared with the values obtained for perfect nanotubes, are of about 43% for the Young's modulus and of about 33% for the shear modulus. On the contrary, the Poisson's ratio increases of about 4 times, compared with that obtained for the perfect nanotube.